Processing Agricultural Waste as complete feed at DZN Farm - Sarjito, S; Muhtadi, M; Wijianto, W; Adiputra, Bagas; Wibowo, Ilham; Aziz, Rizky (Universitas Muhammadiyah Surakarta, 2023)
DZN Farm is a sheep farming group located in the village of Senden RT 10/04, Ngawen, Klaten which has potential in the agricultural sector, especially in the livestock sector. There are 10 breeders with a total of 150 sheep, which have been kept since 2020. One of the potential commodities of Senden village is sheep which are kept as additional income. The DZN Farm livestock group was formed with the aim of ensuring that sheep farmers who are members of the livestock group are able to collaborate with each other, and become a dynamic and growing group. Priority problems faced by partners include: 1) Production aspects including: Quality and availability of feed, namely the decreasing availability of natural animal feed in nature and lack of knowledge of utilizing agricultural waste, Utilization of livestock waste, namely the livestock waste produced has not been utilized optimally; 2) Management and Marketing Aspects, namely Marketing is still semi-conventional, livestock marketing is done by word of mouth between communities and via social media Facebook. The solution for implementing the PKM program is 1) increasing the economic income of livestock groups through engineering complete feed and adding value to livestock waste which is processed into fertilizer. 2) entrepreneurship development which can be achieved through digital-based marketing planning via websites, social media and marketplaces. Meanwhile, the PKM Program's output target is to create an environmentally friendly livestock model to improve the economy.